Physiological aspects and injuries in mixed martial arts - Schlegel, P.; Køehký, A. (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2019)
Mixed Martial Arts (MMA) has become an independent sport discipline with its own distinctive aspects. It can no longer be perceived as before, as a compilation of other martial arts. MMA shows originality in training methods, health aspects, performance requirements or even moral-volitional qualities. The aim of the paper is to analyse the physiological aspects of MMA in both training and combat loads, to discuss the issue of injuries in MMA and to provide a comparison with other martial arts. Studies focusing directly on MMA wrestlers have been selected. These have included both amateur and professional athletes. The databases Pubmed, Scopus, Web of Science, and Scholar were used as sources. MMA ranks among sports with high-intensity workload, wrestlers achieve high levels of lactate and other metabolic markers. They need above-average aerobic capacity and perform well in upper body strength tests. Injury rates in MMA do not differ significantly from those in professional-level martial arts. Most injuries are associated with lacerations on the head. The requirements of extensive workload during performance must be reflected in training. Encouragement of aerobic and anaerobic endurance abilities in conjunction with optimum strength training seems crucial. It is essential to include prophylaxis as regards head concussions and strive for maximum safety of the sportsman during combat. Further research is required to confirm some of the conclusions, the limitations of which are due to the number and quality of the selected studies.